A cross‐sectional epidemiological study of hidradenitis suppurativa in an Irish population (SHIP). (6th December 2017) - Delany, E.; Gormley, G.; Hughes, R.; McCarthy, S.; Kirthi, S.; Markham, T.; Tobin, A.‐M.; Murphy, M.; Kirby, B.
Abstract: Background: Hidradenitis suppurativa (HS), a chronic inflammatory disease that affects apocrine gland–bearing skin, has a significant impact on patients' quality of life. Estimates of the epidemiologic prevalence of HS are highly variable, and clinical data on disease characteristics and patient burden of disease remain limited. Objective: The primary objective of this study was to determine the number of patients with HS attending dermatology clinics in a hospital setting in Ireland (within a 6‐month time period). Secondary objectives included the assessment of disease characteristics and the collection of patient responses on disease burden and work productivity. Methods: This was an epidemiologic, non‐interventional, cross‐sectional study across four dermatology clinics in Ireland over a 6‐month time period. The disease prevalence was estimated by calculating the percentage of total patients with a diagnosis of HS (the primary population) across the selected sites. Secondary analyses were performed using the full analysis set, which consisted of eligible adults (≥18 years of age) from the primary population who provided informed consent. Data from these analyses are presented as descriptive summary statistics, with the use of an analysis of covariance for continuous endpoints. Results: The prevalence of HS across the four selected sites was estimated at 1.4% (95% CI, 1.24–1.62). One hundred and fifty eligible patients comprised the full analysis set. The majority of participants were white (95.3%), female (70.0%), cigarette smokers (56.0%) and overweight or obese (body mass index ≥25 kg/m 2, 81.8%). Most patients for whom data were available presented with Hurley stage II (50.4%), and more than a third of the full analysis set had a relative with HS (34.7%). Questionnaire responses revealed a profound impact on quality of life, including diminished work productivity and various psychological comorbidities. Conclusion: This study offers insight into the clinical features and disease burden of hidradenitis suppurativa in an Irish population.